The application of non-enhanced magnetic resonance thoracic ductography combined with magnetic resonance abdominopelvic scanning in the diagnosis of chylous leakage of the female reproductive system - Meng Huo; Chunyan Zhang; Ling Li; Jianfeng Xin; Xingpeng Li; Yimeng Zhang; Mingxia Zhang; Ying Sun; Lei Sun; Rengui Wang; Yunlong Yue (BMC Medical Imaging)
Abstract Objective To explore the value of non-enhanced magnetic resonance thoracic ductography (NMRTD) combined with MR abdominopelvic scanning in the diagnosis of chylous leakage of the female reproductive system. Methods A retrospective analysis was conducted on the multimodal imaging data from non-enhanced magnetic resonance thoracic ductography (NMRTD), direct lymphangiography (DLG), and abdominopelvic magnetic resonance imaging (MRI) for 18 female patients with reproductive system chylous leakage. Among these patients, 7 had vaginal chylous leakage, 10 had vulvar cutaneous chylous leakage, and 1 had both conditions.The rate of successful visualization of the thoracic duct, the consistency of the drainage directions of the outlet of the thoracic duct, and the degree of visualization of each segment of the thoracic duct by NMRTD and DLG were analyzed. A retrospective analysis was performed on the abnormal manifestations of abdominopelvic MR. Results NMRTD had a significant advantage over DLG in terms of successful visualization of the thoracic duct (94.4% vs. 66.7%, P = 0.035). The display of the drainage directions in the outlet area of the thoracic duct by the two methods showed excellent consistency (kappa value = 0.815) in 12 patients whose outlet areas were visualized by both methods. The degrees of visualization of the upper, middle, and lower segments of the thoracic duct in the NMRTD group were significantly greater than those in the DLG group (P values were 0.02, 0.00 and 0.00, respectively). All 18 patients (100%) showed dilatation of the lymph vessels in the pelvic cavity and retroperitoneum on abdominopelvic MR and DLG as well as pelvic perineal reflux or leakage on DLG. MR revealed multiple-site abnormalities that could not be detected by DLG, including multiple long T1 and long T2 lesions of the spleen in 8 patients (44.4%), of the subcutaneous in 7 patients (38.9%), of the bone in 6 patients (33.3%), perineal lymphedema in 18 patients (100%), and abdominopelvic effusion in 10 patients (55.6%). Conclusion NMRTD combined with abdominopelvic MR has advantages in comprehensively evaluating the thoracic duct and multiple systemic abnormalities in patients with chylous leakage of the female reproductive system.